(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article includes information about one of the most famous novels in Uzbek literature, how it plays a role in the dystopian genre of Uzbek literature. Ahmad Azam, in the introduction to his novel "Dream or Journey to G’uliston" states, "...regardless of what kind of work it turns out to be, whether I call it a story, a novel, or observations, perhaps they are impressions from the journey; if you read it and are aware of the events within, that is enough." He leaves the classification of the genre of the work up to the reader’s interpretation. Although we observe a synthesis of the aforementioned genres in the work, we accept it as a novel due to its artistic scope, the relations between the individual and society encompassing a significant period from a temporal perspective, and finally, its ideological and philosophical aspects. Furthermore, this work also meets the somewhat general and traditional criteria that have been used in literary studies for the novel genre[1].